An Analysis of the Efficacy of Sepia officinalis in the Management of Distress during Climacteric Years - Gupta, Jaya; Das, Biswo Ranjan (Indian Journal of Integrative Medicine, 2021)
Background- Climacteric is the phase in the ageing of women marking the transition from the reproductive phase to the non reproductive state. According to a survey, 44% of post menopausal women used hormonal replacement therapy (HRT). Aim: The present analysis is of the cases prescribed with Sepia officinalis to evaluate its efficacy in DDCY. Method- An open prospective observational study was undertaken by a research institute at six centers for a period of 4 years (including a follow up period of 1 year) as per the protocol. The cases where Sepia (n=53) was found indicated and prescribed were taken up for analysis. The data was analyzed statistically by using the “Wilcoxon sign rank test” on SPSS for the symptoms score and gynecological findings and “t test” for laboratory findings. Results- The mean symptom score at the base line was 13.68 (4.27) and at the end of treatment was 2.81 (2.63), which is statistically significant (P<0.05). Out of 53 patients who completed their follow up, 37 patients showed marked improvement, 14 patients showed moderate improvement and 2 patients showed mild improvement. Forty (40) patients were investigated for FSH both at entry and completion, the FSH value reduced in 24cases. Out of 15 patients who were investigated for lipid profile on completion of the study, the level of lipid cholesterol and Triglycerides (TG) were reduced in 6 patients, HDL was increased in 12 patients which is statistically significant (P=0.024), LDL was decreased in 8 cases and VLDL was decreased in 7 cases. Conclusion-Results of the analysis showed the usefulness of Sepia in management of distress during climacteric years. Further RCT are being conducted to validate the effectiveness of Sepia in DDCY.